Assessing Drug Product Shelf Life Using the Accelerated Stability Assessment Program: A Case Study of a GLPG4399 Capsule Formulation - Dattatray Modhave; Sara Vrielynck; Kevin Roeleveld (Pharmaceutics)
Objective: To evaluate and project the shelf life of GLPG4399, an early-phase clinical drug formulation by applying the Accelerated Stability Assessment Program (ASAP) approach. Methods: Forced degradation conditions were implemented to identify the stability-limiting degradation product. The drug and its degradation products were separated using a validated liquid chromatography method. Then, the selected clinical capsule formulation was placed in a glass vial and exposed to accelerated short-term conditions of combinations of high- and low-level heat and humidity in an open state for 5 weeks. The liquid chromatography results were evaluated using the ASAP, which is based on the moisture-modified Arrhenius principle. The resulting data were fitted using a suitable diffusion kinetics method. Results: The developed model was applied to predict the shelf life of the drug product when using clinically appropriate primary packaging (high-density polyethylene container). The derived stability parameters of the moisture-modified Arrhenius equation were the Arrhenius collision frequency, activation energy, and humidity sensitivity constant. The goodness of fit parameters R2 (>0.95) and goodness of prediction Q2 (>0.80) parameters for the selected model were acceptable. The results of the accelerated, short-term stability study were verified against real-time, long-term 12-month data. Conclusions: We demonstrated the application of the ASAP approach to evaluate the shelf life of a GLPG4399 solid capsule formulation. The studied ASAP approach can be extended to evaluate the stability and shelf-life estimations of other early-phase clinical formulations.